Correlation between Cord Blood Vitamin D Levels and Problem-Solving Neurodevelopment in Early Childhood: A Cohort Study in Rural Indonesia - Stephanie Supriadi; Djatnika Setiabudi; Anindita Noviandhari; Raden Tina Dewi Judistiani; Budi Setiabudiawan; Meita Dhamayanti (MDPI AG, 2022)
Vitamin D influence on brain development and subsequent postnatal neurodevelopment remains controversial. We explored the correlation between cord blood vitamin D levels and longitudinal neurodevelopment in early childhood. A cohort study was conducted on term infants with no congenital abnormalities, born from pregnant women from a cohort study. Cord blood samples were collected to measure vitamin D. Neurodevelopment was examined three times in infants aged 6, 12 and 24 months using the Ages and Stages Questionnaire-3, which comprises 30 questions of five developmental domains: gross motor, fine motor, communication, problem-solving and social-personal. Statistical analysis was conducted with Spearman's rank correlation and multiple linear regression. Of the 141 babies born from previous cohort studies, only 116 participants were included. The mean level of cord blood vitamin D was 16.2 ng/mL. The percentage participants with vitamin D deficiency and insufficiency were 12.9 and 65.5, respectively. Cord blood vitamin D and the problem-solving domain for infant aged 12 and 24 months were correlated (r = 0.217 and 0.414, respectively). Multiple linear regression showed a decreased problem-solving domain score of 0.641 associated with decreased vitamin D levels. In conclusion, cord blood vitamin D levels correlated with infant neurodevelopmental status.